ENTRE LIMITES E POSSIBILIDADES: O ESTUDO DOS GÊNEROS JORNALÍSTICOS NAS FRONTEIRAS DE MATO GROSSO DO SUL - Pereira, Clarissa Josgrilberg (2013)
It is in Mato Grosso do Sul, where the largest city with land border in the country is located, Ponta Pora, as well as the city of Corumbá as the main connecting route to Bolivia. This study aims to analyze the profile of the printed newspapers of the two major border cities in Mato Grosso do Sul, through the diagnosis of journalistic genres present in this type of frontier media. This choice is due to the fact that these places are not constant targets of research, there are few studies in the area of communication related to boundary issues, as far as we know, none of those connects that location with the production of journalistic genres. Through morphological analysis, we analyzed the sample (obtained by the technique constructed week) of major newspapers on this border area, in order to identify what are the journalistic genres present in the newspapers in question and how they constitute an area of intense cultural exchange. In the Paraguayan border, the studied newspapers were Jornal Regional and ABC Color and in the Bolivian border, the newspapers Gazeta Corumbaense and La Estrella del Oriente. Interviews with journalists from those newspapers were also conducted to understand the production of genres, as well as, by way of illustration, we interviewed some readers of the aforementioned way of communication to understand their vision and find out what are their preferences concerning journalistic genres. Among the results, we have that the boundary matter is not news at the border and that the backwoods characteristic of the media interferes more in news production than the unusual cultural setting of the border.